Isolation, screening and molecular identification of bioflocculants–producing bacteria - ASSALA MOHAMMED AL KHAFAJI; ASIA FADHILE ALMANSOORY; NASSIR ABDULLAH ALYOUSIF (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Al Khafaji AM, Almansoory AF, Alyousif NA. 2023. Isolation, screening and molecular identification of bioflocculants–producing bacteria. Biodiversitas 24: 4410-4417. Bioflocculants are biological compounds produced by different microorganisms with many applications for wastewater treatment as such become an important product in biotechnology and a consequence to be used in industries. The current study aimed to isolate, identify, and screen bioflocculant-producing bacteria from different sites in Basrah City in Iraq. The production of bioflocculants was enhanced by optimization of various cultural conditions such as (carbon source, nitrogen supply, pH, and inoculum sizes) which were estimated in terms of flocculating activity test. Four wastewater samples and oil- contaminated soil samples were collected. Twenty-one different bacteria were isolated from wastewater and soil. Eleven bacterial isolates showed flocculating activity values of more than 50 %. The results showed that two bacterial isolates were reported as the best bioflocculants-producing isolates with a flocculating activity value of 87.80 % and 81.38 % respectively, these two isolates belonged to Aeromonas simiae and Exiguobacterium profundum which identified by 16S rDNA gene sequencing. Four bacterial isolates were discovered and recorded as new strains in NCBI GenBank with the accession numbers OQ848055 (Escherichia coli strain ANABASR1), OQ848056 (Stutzerimonas balearica strain ANABASR2), OQ848057 (Bacillus jeotgali strain ANABASR3) and OQ848058 (Hydrogenophaga temperata strain ANABASR4). The maximum flocculating activity of 84.49% and 88% was reported for A. simiae and E. profundum respectively under optimum conditions (glucose as carbon source, (NH4)2SO4 as nitrogen source, pH= 7 and 5% inoculum size). The phylogenetic tree was created in the current study based on 16S rDNA gene sequences of bioflocculants –producing bacteria to assess their close relationship and evolution.